Aspects of planning civil engineering construction - Los, Ronald Peter (Department of Civil Engineering, 2016)
The process of management is a continuous process of planning, organising, co-ordinating, motivating and controlling according to Pilcher. In any competitive construction organisation the objective of the managerd.al, staff is mainly to ensure that the firm's resources are utilised both effectively and efficiently. In this thesis certain aspects relating to the planning and control of a contractor's resources on a Civil Engineering contract are considered.